Augmentation strategy fluoxetine and lurasidone in the treatment of OCD with comorbid Restrictive Anorexia: a case report. (1st June 2022) - Orsolini, L.; Bellagamba, S.; Tempia Valenta, S.; Salvi, V.; Volpe, U.
Abstract : Introduction: Obsessive-Compulsive Disorder (OCD) is characterized by the presence of intrusive thought (obsessions) and ritualistic behaviour (compulsions). First-choice psychopharmacological treatment is based on serotonin reuptake inhibitors (SRIs). However, about half of OCD do not or partially respond to SRIs (TR-OCD) and need an augmentation strategy with second-generation antipsychotics (SGAs). Objectives: We report a case of severe OCD with comorbid anorexia nervosa, restrictive type (AN-r) treated with fluoxetine (up to 40 mg daily) and lurasidone (37 mg daily bedtime) augmentation. Methods: At baseline and monthly 4-months-follow-up were administered Y-BOCS-II (Yale-Brown Obsessive Compulsive Scale), CGI-S (Clinical Global Impression-Severity), SCL-90 (Symptom Checklist-90 items) and EDI-3 (Eating Disorder Inventory-3). Results: Compared to the baseline, a clinically significant clinical response was observed on OC at Y-BOCS-II (≥35% Y-BOCS reduction) and eating symptomatology at EDI-3 after 1 month of augmentation treatment, while a full remission after 3 months (Y-BOCS scoring ≤ 14)(p<0.01). We also noticed, throughout clinical follow up interviews, improvement in patient's social skills and life satisfaction. Conclusions: Further longitudinal and real-world effectiveness studies are needed to confirm these preliminary findings and investigate the potential of lurasidone augmentation strategy in attenuating OC symptomatology in TR-OCD and whereas a comorbid AN-r is present. Disclosure: No significant relationships.